Формування товарної інноваційної політики на підприємствах молочної галузі - Васютинська, Юлія Олегівна (My University, 2021)
Дисертаційна робота присвячена дослідженню теоретичних, методичних та практичних питань формування товарної інноваційної політики підприємства. В роботі поглиблено понятійно-категоріальний апарат процесу формування товарної інноваційної політики, визначено місце нового товару, розглянуто суть новизни товару та визначено рівні новизни. Досліджено інноваційну активність підприємств харчової промисловості в цілому та молочної галузі зокрема, визначено основні тенденції їх інноваційної діяльності. Товарно-інноваційна діяльність розглянута на прикладі п’яти підприємств молочної галузі. Запропоновано методичний підхід до оцінки ступеня та рівня новизни нових товарів за видами новизни, визначення значущості новизни для виробника та визначення класів новизни для обґрунтуванням товарного асортименту для формування товарної інноваційної політики. За визначеними класами новизни запропоновані управлінські дії щодо визначених груп товарів. Ключові слова: товарна інноваційна політика, новий товар, новизна товару, рівень новизни товару, ступінь новизни товару, значущість новизни товару. The issue of formation of commodity innovation policy is considered taking into account the development of modern economic science and industrial activity practice. Considering the essence of the implementation of enterprise policy, the substantive essence of the concepts of "product" and "innovation" the concept of product innovation policy is defined as a set of strategically directed, marketing-oriented actions, methods and principles of the enterprise related to market research, development, manufacture, marketing, after-sales service and withdrawal from production of new goods and activities aimed at providing more progressive, cost-effective level of organization of production and management through the use of new technologies, new types of raw materials, introduction of fundamentally new methods of conquering and expanding markets. This policy should lead to the full consistency of the manufacturer's goals and consumer`s requirements. The conceptual and categorical apparatus of the process of formation of commodity innovation policy is deepened in the work, the place of a new product is determined, the essence of product novelty is considered and the novelty levels are determined. For the effective formation of product innovation policy, the issue of product novelty was studied, the classification of new products by level of novelty, classification of types and levels of product novelty, which divides novelty by its functional orientation, was expanded. This allowed us to determine the main components of the proposed types of novelty and thus form a structure of novelty of the product, to offer indicators for assessing the novelty of goods for each of its types. In order to determine the prerequisites for the formation of commodity innovation policy, the innovative activity of the food industry in general and of the dairy industry in particular is studied, the main trends of their innovation activities are identified. Commodity-innovation activity is considered on the example of five enterprises of the dairy industry. The analysis allowed us to note that all companies are actively introducing new products with different levels of novelty, organize their innovation activities differently in accordance with the innovation strategy and market position. The defined qualitative characteristics of innovative changes of new goods allowed us to determine the level of changes for each group of goods. A methodical approach to assessing the degree and level of novelty of new products by the types of novelty, determining the significance of novelty for the manufacturer and determining the classes of novelty to justify the product range for the formation of product innovation policy is proposed. According to certain classes of novelty, management actions are proposed for certain groups of goods. In order to ensure informed decisions on the formation of the product range, methodological tools for assessing the level of significance of product novelty is proposed as a measure of the importance of product novelty for the formation of the optimal product range in the product innovation policy of the enterprise. The proposed methodological tools are based on the developed criteria for determining the level of significance of the product for the company, taking into account the importance of the level of novelty for each company, ranking the product range of new products by the method of multicriteria decisions TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). This allowed us to group new products according to the level of significance of their novelty to determine priorities during the substantiating the product range. The study of the main components and stages of formation of commodity innovation policy from the standpoint of process-functional approach allowed to propose the formation of commodity innovation policy to be considered as a process of interaction of three blocks: the unit for studying the external environment, the unit for determining the internal capabilities of the enterprise and the unit for implementing the actions of product innovation policy.
Keywords: кафедра вищої математики імені проф. Можара В. І.; товарна інноваційна політика; новий товар; новизна товару; рівень новизни товару; ступінь новизни товару; значущість новизни товару; commodity innovation policy; new product; novelty of goods; level of novelty of goods; degree of novelty of goods; significance of novelty of goods